The Story of the People of the Cave (Ashabul Kahf) in the Qur’an: A Stylistic Study of Surah Al-Kahf - Laeli, Alfil; Janah, Siti Zahrotul; Azzahra, Zulfaa Hadi (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
The story of Ashabul Kahf in Surah Al-Kahf (verses 9–26) presents a narrative rich in rhetorical beauty and profound moral messages. This study employs a descriptive-qualitative method using a stylistic approach to uncover the linguistic elements that enhance the narrative's power. The analysis focuses on aspects such as rhythm and cadence, khiṭāb inshāʾī (performative expressions), kalām khabarī (declarative statements), dialogue (ḥiwārī), waṣl (cohesive devices), muqābalah (contrast), jinās (paronomasia), majāz mursal (metonymy), and ījāz (concise expression).The aim of this study is to explore the implicit meanings, narrative structure, and linguistic uniqueness that enrich the spiritual and theological messages of the story. The findings show that the consistent end-rhyme of the verses creates acoustic harmony, while the use of khiṭāb inshāʾī and kalām khabarī adds aesthetic and rhetorical value. The dynamic dialogues (ḥiwārī), the use of waṣl for flow cohesion, and muqābalah highlighting dual meanings further enhance the narrative’s beauty. Rhetorical devices such as jinās and majāz mursal add depth to the meanings, while ījāz demonstrates effective conciseness without losing substance.Altogether, these elements affirm that the story of Ashabul Kahf not only conveys a moral message but also presents linguistic beauty that stands as one of the Qur’an’s literary miracles. These findings are expected to contribute to Qur’anic studies through the lens of stylistics.